THE EXPERIENCE AND CONSEQUENCES OF THE GENOCIDE(S) AGAINST ARMENIANS - Hofmann, Tessa (Armenian Folia Anglistika, 2025)
My contribution deals with different but interrelated aspects of the historical and contemporary Armenian experience of genocide. I point out the significance of the Ottoman genocide against Armenians for the coining of the term genocide and the UN Genocide Convention. I also examine the assessment under international law of the nine-month-long starvation blockade against the Republic of Artsakh, the military attack on 19 September 2023 in violation of international law and the expulsion of the population. What are the effects of repeated experiences of genocide, loss of homeland (“patricide”) and international indifference? In the third part of my article, I examine the Azerbaijani genocide accusations against Armenia in the context of the historical and political facts and explore the question of whether Azerbaijanis in the Republic of Armenia were “collateral victims” (de Waal, 2013, p. 75) of the Ottoman genocide against the Armenians. Which were and are the consequences of the equation of Turks and Azerbaijanis? Is this really a case of “one nation in two states” (Heydar Aliyev) or an identity problem of the Turkic-speaking, predominantly Shiite population in the south-eastern Caucasus? And how should early genocidal declarations of intent by state politicians of Azerbaijan be interpreted? What about the culture of remembrance in post-Soviet Azerbaijan, which has erected museums and memorials analogous to Armenia’s culture of remembrance – perhaps in imitation of it – to support its genocide accusation against Armenia.